Delivery of Radioiodine Ablation in a Patient with End-Stage Renal Disease - Andrew T. Bussey; Aung Tin; Neil Hoye; Mark Richardson (World Journal of Nuclear Medicine)
This case presents a pragmatic approach to the management of a radioiodine remnant ablation patient on hemodialysis which required no pretherapeutic dosimetric measurements. Pretreatment radiation dose modeling was performed using literature values for radioiodine hemodialysis extraction efficacies to determine a safe treatment regimen including adjustment of the administered activity and hemodialysis frequency. The pretreatment modeling was subsequently verified using external and blood radiation monitoring during treatment.